Longitudinal online diaries with dental practitioners and dental care professionals during the COVID-19 pandemic: A trajectory analysis - Beaton, Laura; Knights, Jennifer; Barnsley, Lorna; Araujo, Mariana; Clarkson, Jan; Freeman, Ruth; Young, Linda; Yuan, Siyang; Humphris, Gerry (Frontiers in Oral Health, 2022)
Introduction: The COVID-19 pandemic resulted in a series of significant changes and adjustments within dentistry. Recent research has illustrated the impact of the pandemic on the dental profession, indicating that many dental professionals felt emotionally exhausted and experienced significant uncertainty and anxiety. This qualitative study aimed to understand how these experiences and emotions changed over the course of six months, in dental trainees and primary dental care staff in Scotland. Methods: A longitudinal diary study was conducted (June – December 2020) with dental trainees and primary dental care staff. The diary asked respondents to answer three questions related to their emotional exhaustion, on a weekly basis. Respondents were also asked to describe any significant issues or concerns they had experienced during the preceding week because of the impact of the COVID-19 pandemic on their work or training. This qualitative data was explored using a trajectory analysis approach to determine changes over time. Results: Several key concerns were prevalent amongst respondents, which fluctuated over time. Concerns included: the impact of the pandemic on respondents’ future careers and on dentistry; adapting to new working environments; the impact on their patients’ dental treatment; the impact on their health and wellbeing; financial considerations and adjusting to new safety measures as part of the remobilization of dental services. Discussion: This longitudinal diary study has shown some parts of the dental profession in Scotland expressed very varied and personal concerns and anxieties related to COVID-19. Respondents’ candor in their diary entries revealed explicit, frequent and high levels of uncertainty and worry related to their training and career. The data corpus highlighted the emotional toll these anxieties have taken on the dental professions in Scotland. Conclusion: These findings demonstrate the need for (a) increased provision of mental health and wellbeing support services for dental staff and (b) the study of the linkage between organization of pandemic management to the working practices of staff delivering services. Interventions, at various levels, should take into consideration the fluctuating nature of dental professionals’ concerns and anxieties over time, to address both immediate and longer-term issues.